CULTURAL IDENTITY NEGOTIATION IN NGUYEN’S “THE AMERICANS” - Fitria, Sari; Llyoid, Paras Vincenct L.; Kusumoriny, Laksmy Ady (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The study scrutinizes the negotiation of a person’s cultural identity in Viet Thanh Nguyen's short story, “The Americans”. As a diaspora, Nguyen wrote the character of Claire Carver in “The Americans” as a concrete depiction of a diaspora who struggles with negotiating cultural identity. This negotiation is depicted by tensions between Claire (a second generation of a multiracial family), who missed her Asian identity, and his father, who wants her to retain American identity. Therefore, this study explores the homeland (Asia) and host land (America) position in this diaspora character. The cultural identity and diaspora concept by Stuart Hall is applied to critically assess the identity negotiation experienced by the character in the short story. Then, this study applies the content analysis method. The data forms are sentences that indicate identity negotiation. The findings of the study indicate that the diaspora character engages in cultural identity negotiation, which involves American cultural identity of her father as the one who dominates her to embrace American identity and her Asian cultural identity, Vietnamese, as the effect of confusion of her cultural identity since she is a mixed race of black American and a Japanese. This study thus suggests that a further study that celebrates the diaspora’s identity may participate in cherishing the diversity.